A Disintegrin and Metalloproteinase—Control Elements in Infectious Diseases - Aljohmani, Ahmad; Yildiz, Daniela (Frontiers in Cardiovascular Medicine, 2020)
Despite recent advances in treatment strategies, infectious diseases are still under the leading causes of death worldwide. Although the activation of the inflammatory cascade is one prerequisite of defense, persistent and exuberant immune response, however, may lead to chronicity of inflammation predisposing to a temporal or permanent tissue damage not only of the site of infection but also among different body organs. The initial response to invading pathogens is mediated by the recognition through various pattern-recognition receptors along with cellular engulfment resulting in a coordinated release of soluble effector molecules and cytokines aiming to terminate the external stimuli. Members of the ‘a disintegrin and metalloproteinase’ (ADAM) family have the capability to proteolytically cleave transmembrane molecules close to the plasma membrane, a process called ectodomain shedding. In fact, in infectious diseases dysregulation of numerous ADAM substrates such as junction molecules (e.g. E-cadherin, VE-cadherin, JAM-A), adhesion molecules (e.g. ICAM-1, VCAM-1, L-selectin), and chemokines and cytokines (e.g. CXCL16, TNF-) has been observed. The alpha-cleavage by ADAM proteases represents a rate limiting step for downstream regulated intramembrane proteolysis (RIPing) of several substrates, that influence cellular differentiation, cell signaling pathways and immune modulation. Both the substrates mentioned above and RIPing crucially contribute to a systematic damage in cardiovascular, endocrine and/or gastrointestinal systems. This review will summarize the current knowledge of ADAM function and the subsequent RIPing in infectious diseases (e.g. pathogen recognition and clearance) and discuss the potential long-term effect on pathophysiological changes such as cardiovascular diseases.